Gap detection thresholds in 1/3-octave white noise centered at 4kHz in children 7-14 years of age with normal hearing and with very high frequency sloping hearing loss - Jaroszewski, A.; Jaroszewska, A. (Archives of Acoustics, 2001)
Gap detection thresholds in 1/3-octave white noise were measured in primary school children aged 7-14 with normal hearing and with very high frequency sloping hearing loss. The results show median gap detection thresholds, in the group of normal hearing children of 5.5ms, while in the group of hearing impaired median gap detection thresholds are five times larger, i.e. 25.5ms, reaching 50ms in some cases.